Border Architecture: Rethinking the Future - Vaquera, Pedro (My University, 2020)
The contemporary perspective of the U.S.- Mexican border can be defined by the current condition of a division and separation of nations. While the political border is clearly defined, the cultural border is very complex. Taking into consideration more than the traditional definition of borders, this thesis explores other types of barriers dividing the U.S. and Mexico, including cultural, economic, and educational obstacles. The political border is often separate from the physical barrier, and the spaces in-between creates the potential for the exchange of knowledge, culture, and commerce, redefining the socio-cultural identity of the region on either side of the border. The analysis and complex exploration of border architecture will focus on the San Diego / Tijuana border region. This border plays a significant role in the context of the region, with its vast urban sprawl on both sides and varying physical characteristics. The exploration will investigate and develop spaces that will allow users to connect and communicate through different levels of separation and unique physical conditions. Therefore, changing not only the perception of identity but creating new opportunities for bi-national interactions.
Thesis (Master's)--University of Washington, 2020
Keywords: Architecture; Border Architecture; Future; Architecture; Architecture